2015
DOI: 10.1093/jme/tjv142
|View full text |Cite
|
Sign up to set email alerts
|

Larval Habitats Diversity and Distribution of the Mosquito (Diptera: Culicidae) Species in the Republic of Moldova

Abstract: A countrywide field survey of immature mosquitoes was conducted in Moldova with the aim to evaluate the Culicidae species composition in different larval habitats and their distribution in the country. In total, 259 potential larval habitats were sampled in the 53 localities, resulting in 9,456 specimens. Twenty species belonging to the genera Anopheles, Aedes, Culex, Culiseta, and Uranotaenia were collected. Mean species richness in aquatic habitats ranged from 1.00 to 4.00, and, for example, was higher in sw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…Generally, an increase in mosquito breeding habitats results an increase in vector density and eventually leading to increased malaria transmission [25,26]. Most of the mosquito breeding habitats identified in this study were previously reported elsewhere [13,27,28]. However, the nature and formation of some of the habitats made them specific and unique to the study area and thus can be target for intervention.…”
Section: Discussionmentioning
confidence: 57%
“…Generally, an increase in mosquito breeding habitats results an increase in vector density and eventually leading to increased malaria transmission [25,26]. Most of the mosquito breeding habitats identified in this study were previously reported elsewhere [13,27,28]. However, the nature and formation of some of the habitats made them specific and unique to the study area and thus can be target for intervention.…”
Section: Discussionmentioning
confidence: 57%
“…Immature stages of the species can be found from May to October across a variety of habitats, both in natural and urbanized areas [ 3 5 ]. Thus, larvae occur mostly in stagnant permanent, fresh or slightly brackish (up to 1000–1100 mg/l) water bodies, often overgrown with higher aquatic vegetation [ 5 – 8 ]; occasionally, they have also been found in more ephemeral environments such as rice paddies, puddles, hoof prints, and artificial containers [ 3 , 9 , 10 ]. Associations with instars of the following mosquito species have been recorded in the literature: Anopheles algeriensis , An.…”
Section: Introductionmentioning
confidence: 99%
“…longiareolata , Cs. subochrea , and Ochlerotatus caspius [ 3 , 5 – 8 , 11 – 16 ], which evidently suggest a broad ecological plasticity of Ur. unguiculata .…”
Section: Introductionmentioning
confidence: 99%
“…Cx. pipiens mosquitoes can live in permanent aquatic environments, such as ground pools (Amini et al, 2020, Barr, 1967, Dida et al, 2018, Sulesco et al, 2015), ponds (Lühken et al, 2015), stream edges (Amini et al, 2020), and lake edges (Vinogradova, 2000) that are more common in rural areas, but Cx. pipiens are also found in urban and suburban residential areas, where they typically breed in artificial containers (Sulesco et al, 2015), including tires (Lühken et al, 2015, Nikookar et al, 2017, Verna, 2015), rainwater tanks (Townroe and Callaghan, 2014), and catch basins (Gardner et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…pipiens mosquitoes can live in permanent aquatic environments, such as ground pools (Amini et al, 2020, Barr, 1967, Dida et al, 2018, Sulesco et al, 2015), ponds (Lühken et al, 2015), stream edges (Amini et al, 2020), and lake edges (Vinogradova, 2000) that are more common in rural areas, but Cx. pipiens are also found in urban and suburban residential areas, where they typically breed in artificial containers (Sulesco et al, 2015), including tires (Lühken et al, 2015, Nikookar et al, 2017, Verna, 2015), rainwater tanks (Townroe and Callaghan, 2014), and catch basins (Gardner et al, 2012). Artificial containers are less likely to harbor larger predators, such as freshwater fish (Cyprinidae and Poeciliidae), salamander larvae (Ambystomatidae), dragonfly larvae (Aeshnidae), and backswimmers (Notonectidae) because temporary aquatic environments cannot support the relatively long development times of these organisms.…”
Section: Discussionmentioning
confidence: 99%